Attitudes of Future Music Teachers to the Opportunities of Reflective Teaching/Learning - Šiupinytė, Justina; Kavaliauskienė, Angelė (Jaunųjų mokslininkų darbai, 2021)
The article analyses reflective learning, discusses the levels of reflective teaching/learning and its methods. The purpose of the study ̶ to reveal the attitudes of future music teachers to the opportunities of applying reflective teaching/learning. The following tasks were set to achieve the objective of the investigation: 1) define the concept of reflective teaching/learning; 2) discuss the methods of reflective teaching/learning; 3) empirically explore the attitudes of future music educators to the opportunities of applying reflective teaching/learning. Research methods: analysis of scientific literature, analysis of the results of a questionnaire survey. The study, carried out in April 2019, involved 37 future music teachers. A questionnaire survey was intended to reveal attitudes of future music teachers to the relevance of reflection in their professional development, views on the most effective reflection methods and the opportunities of applying reflective pracices in music education. Analysis of scientific literature suggests that reflective teaching is a process where experience is transformed into learning. Practicing reflective learning, you can monitor your personal growth and find ways to improve the learning to learn process. The study revealed that the most successful solutions can be found practicing reflection, analysing teaching experiences. Reflection methods used in training and developing future teachers ensure process personalization and assessment of personal progress. The most successful methods of reflecting professional experiences are writing a diary, free associations and structured discussions. An empirical study revealed that future music teachers believe that mostly reflection helps them analyse their own learning, develops critical thinking and promotes academic and professional growth. In the respondents’ opinion, the most relevant reflection method to be used in both the education process and in future music teacher training is a structured discussion. The respondents pointed out that reflection used in music education enables the teacher to identify and assess his/her mistakes, teaches children to assess their own musical abilities, and draws on the teacher’s creativity. The study showed that reflective practices are one of the most important factors, that help the teacher, a life-long learner, consistently innovate, rethink his/her practices and contributes to personal growth.